Improving the Analysis of Profitability Indicators in Motor Transport Enterprises - Khotamov, Komil Rabbimovich; Kalonov, Mukhiddin Bakhriddinovich; Kadirovich, Rizaev Nurbek; Ismailovich, Khusinov Ibragim (The journal of contemporary issues in business and government, 2021)
This article describes the profitability and some other financial indicators reflecting the level of profitability of enterprises, as well as some issues in their calculation. Including, conclusions and recommendations are given based on the results of a study of the composition of indicators used to determine the rate of return.